2018
DOI: 10.1039/c7mh01138e
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional water delivery on a superhydrophilic surface with two-dimensional asymmetrical wettability barriers

Abstract: A superhydrophilic surface decorated with 2D hydrophobic water barriers is proven to be a potential platform for unidirectional liquid transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…

properties assisted in moisture absorption. [7] Inspired by nature, researchers have developed artificial water harvesters, [7][8][9][10][11][12][13][14][15][16][17][18] such as water collecting filaments and hydrophobichydrophilic patterned fog collectors. [3][4][5][6] These excellent water harvesting creatures elucidate the critical role of wettability irregularity and hierarchical structure gradient in guiding water transport.

…”
mentioning
confidence: 99%
“…

properties assisted in moisture absorption. [7] Inspired by nature, researchers have developed artificial water harvesters, [7][8][9][10][11][12][13][14][15][16][17][18] such as water collecting filaments and hydrophobichydrophilic patterned fog collectors. [3][4][5][6] These excellent water harvesting creatures elucidate the critical role of wettability irregularity and hierarchical structure gradient in guiding water transport.

…”
mentioning
confidence: 99%
“…Wetting is one of the basic characteristics of solid surfaces. It is very important for processes like adhesion [1], selfcleaning [2], fluid drag reduction [3], heterogeneous nucleation [4], and the formation of coffee rings [5]. Therefore, it has attracted immense interest in a large diversity of research fields ranging from physical, biological, and environmental sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Learning from the nature, researchers found that the Namib Desert beetles and Texas horned lizard drive the one-way transmission of water droplets in foggy conditions on their typical bumpy backs with alternating hydrophilic and hydrophobic regions; the honeycomb surface of the scales increases the surface roughness and support more condensation foci to survive [8][9][10][11]. By exploring the creatures with excellent directional water transport ability, tremendous methods in attempting to prepare artificial materials with excellent directional water transport or capture capability have been proposed [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%